Teaching Writing Paragraph Using Roundtable Technique - Mentari Pratami; Dewi, Erniyanti Nur Fatahhela (EDULIA: English Education, Linguistic and Art Journal, 2026)
To facilitate writing paragraph in an effective, efficient and enjoyable way, a lecturer applied roundtable technique. The purpose of the research is to find out: 1). whether the implementation of the roundtable technique effective for writing paragraph, 2). the strength and weakness of the technique, and 3). students’ response on the use of roundtable technique. After been applied to 30 students of Bina Sarana Informatika University semester 1 academic year 2025/2026 it was found out that the technique was effective to practice writing paragraph. After students were engaged to several practice on writing paragraph, finally their skill was improved. Roundtable technique created good learning atmosphere such as; peer learning, encouraging students to write on their own, building autonomous learning, fun learning, and resulting active learning. On the process of roundtable technique, students responded the activity positively. Since, the roundtable technique had contributed to the writing skill on paragraph, it is suggested to use roundtable to facilitate writing practice such as; writing types of text, essay, and other writing lesson. One paragraph, consist of objective of the research, research method, finding, and conclusion.   Keywords: EFL Students, Paragraph Writing, Roundtable Technique, Writing Skill.